ABO-Incompatible Robotic-Assisted Kidney Transplantation in the Obese Recipient - Prudhomme, Thomas; Del Bello, Arnaud; Sallusto, Federico; Lesourd, Marine; Kamar, Nassim; Doumerc, Nicolas (Frontiers in Surgery, 2020)
Objective: The objective of this preliminary study was to report and compare the peri-operative and functional results of ABO-incompatible (ABOi) living-donor robotic-assisted kidney transplantation (RAKT), ABO-compatible (ABOc) living-donor RAKT and ABOi living-donor open kidney transplantation (OKT). Materials and Methods: For the present retrospective study, we analyzed data of consecutive patients who underwent ABOi or ABOc-RAKT and ABOi-OKT, from January 2015 to December 2019, in one French academic center. Patients’ baseline characteristics, operative and functional outcomes were compared between ABOi-RAKT, ABOc-RAKT and ABOi-OKT. Results: 29 RAKT, including 7 ABOi-RAKT, and 56 ABOi-OKT were performed in our center. Median follow-up was 2.0 years. Median recipient age, pre-emptive kidney transplantation rate, sex ratio and desensitization procedures were similar in ABOi-RAKT, ABOc-RAKT and ABOi-OKT groups. Recipient BMI at transplantation was statistically higher in ABOi and ABOc-RAKT groups compared to ABOi-OKT. The surgical site complication (principally infection-related) rate was lower in ABOi-RAKT, without statistical differences (0% vs. 8.9% respectively in ABOi-RAKT and ABOi-OKT, p=0.7). The delayed graft function rate was 0% in ABOi-RAKT, 13.6% in ABOc-RAKT and 10.7% in ABOi-OKT (p=0.6). The post-transplantation blood transfusion rate was statistically higher in the ABOi-OKT group (14.3% versus 13.6% versus 57.1% in ABOi-RAKT, ABOc-RAKT and ABOi-OKT, respectively, p=0.001). The kidney graft survival at 1 month and at last follow-up was not different between ABOi-RAKT and ABOi-OKT. Conclusion: Our data support the use of ABOi-RAKT to restore accessibility to kidney transplantation for obese patients to the greatest extent possible. Large series are required to confirm these encouraging data from a single center.